Pengaruh Keterampilan Diskusi Kelompok Melalui Model Pembelajaran Two Stay Two Stray Pada Mahasiswa Semester 1 Jurusan Teknik Mekanik Politektik Teknologi Kimia Industri Medan Tahun Pembelajaran 2021-2022 - Sorta Lumbantoruan (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
The Two Stay Two Stray learning model can help students become more active during learning and students also better master the problems discussed. Two Stay Two Stray is a cooperative learning model that provides opportunities for groups to share results and information with other groups. In learning with this model, students are taught to actively conduct group discussions and work together to discuss a problem. In this cooperative learning, the development of study groups is made heterogeneous in terms of academic ability, gender, race, ethnicity, and so on so that they can know each other who needs help and who can provide assistance. Emphasis is not only on completing tasks, but also interpersonal relationships (relationships between individuals who respect each other). Based on the results of the study, the discussion activities carried out using the Two Stay Two Stray learning model showed maximum results. The students were very good at the courage aspect and seemed eager to have discussions. In the aspect of speech clarity, there has been a good improvement. Students have paid attention to the structure of sentences and the choice of words used. Students are also good at expressing opinions accompanied by rational reasons. The increase in results/products can be seen from the ability to discuss students before being subjected to action and after being subjected to action. At the time of the pre-action test, the student's score was still low. Students still look silent, shy, and less active in discussing. Students lack the courage to convey ideas/arguments and are less fluent in speaking. After being subjected to action, the student's ability has improved well. The results of this study indicate that there is an effect of the Two Stay Two Stray learning model on group discussion skills in Indonesian subjects in order to help improve the discussion skills of Semester 1 Students of Politeknik of Chemical Engineering, Medan Chemical Industrial Technology Polytechnic, for the 2021-2022 academic year.Keywords: Two Stay Two Stray learning model, group discussion skills.